Perforation of Meckel's diverticulum by an intact fish bone. (20th February 2013) - Mouawad, Nicolas J; Hammond, Stephen; Kaoutzanis, Christodoulos
Abstract : Meckel's diverticulum is the most common congenital anomaly of the gastrointestinal tract, with an overall incidence of approximately 2.2%. It is generally noted incidentally during laparotomy for management of other abdominal pathology. Complications are infrequent, developing in 4% of individuals with this abnormality, and are usually seen in childhood. Herein, we discuss the case of a 52-year-old Caucasian man presenting with a 1-day history of worsening central and right-sided abdominal pain. Initial evaluation posed a broad differential however, following conservative measures and unremarkable plain films, the patient developed peritoneal signs necessitating operative intervention. During diagnostic laparoscopy, a Meckel's diverticulum was noted to be inflamed and perforated by an intact fish bone. The patient was treated successfully with a segmental resection and primary anastomosis, and had an uneventful postoperative recovery.